Successful innovation systems : a resource-oriented and regional perspective for policy and practice - Garzik, Ludovit (Future of business and finance,, 2022)
This book places a central question: why are some regions in the world more successful in innovation than others? It aims to increase readers' understanding of how innovation processes are accelerated or hindered by regional characteristics. A deep dive into differences of innovation ecosystems across global regions will provide a detailed mosaic of strengths and weaknesses. The audience will also learn to assess the resources and elements of regional innovation systems and to compare and contrast structures and processes in innovation management in Africa, Asia, Europe, and the Americas. The speciality of the book lies in its focus on the patterns that are behind the development of many successful innovation regions and it defines the ingredients for right planning and policy development.